PERNIKAHAN DINI DAN DAMPAKNYA (TINJAUAN BATAS UMUR PERKAWINANMENURUT HUKUM ISLAM DAN HUKUM PERKAWINAN INDONESIA) - Hasan Bastomi (Program Studi Hukum Keluarga Islam, 2016)
This library research article discusses child marriage in Indonesia usingcontent analysis of marriage regulations. It is also addresses consequences of child marriage. Marriage regulations open the possibility of childmarriage in case of necessity. This is an implementation of sad al-zari‟ahin order to prevent the bigger problems. However, child marriage oftenbrings negative impacts for the bride socially, economically andpsychologically.